Application of Blended Learning to Increase Mathematics Learning Outcomes from Beginning Mathematics Ability - Jemakmun Jemakmun (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2022)
The purpose of this study was to determine the effect of the blended learning model, with formative and summative assessments in terms of early mathematics abilities on the mathematics learning outcomes of high school students in the city of Palembang. Blended Learning Model, Types of assessment include formative and summative, early math skills include high and low. The method used is quasi-experimental, while the design used is treatment by level 2x2x2. The results showed that there was a significant improvement in the blended learning model with formative and summative assessments in terms of high and low early mathematics abilities on students' mathematics learning outcomes. Next; (1) a Blended learning model with formative assessment, can improve students' mathematics learning outcomes at high and low early math abilities, and (2) a blended learning model with summative assessment, can improve students' mathematics learning outcomes at high early math abilities.